Klasifikasi Serangan Jaringan untuk Investigasi Forensik Jaringan: Tinjauan Literatur - Muhamad Maulana; Ahmad Luthfi; Dwi Kurnia Wibowo (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2023)
The computer network plays an important role in supporting various jobs and other activities in the cyber world. Various kinds of crimes have often occurred on computer networks. It is very demanding to build a computer network architecture that is safe from attacks to protect the data transacted. If there has been an attack on the computer network, of course, further investigation must be carried out to identify the attacker and the motive for the attack. An additional need is to evaluate the security of the network. This article reports a systematic review of the literature aiming to map the classification of attacks on computer networks and map future research. Based on the exploration, 30 key studies were selected that reveal the mapping of attack classifications on computer networks. The results of the literature review show that attacks on computer networks vary widely. Based on the results of the literature review conducted, it produces a roadmap for future research, which is to classify attacks on computer networks using a machine learning approach. The use of machine learning serves to help classify and investigate the needs for attacks on computer networks. The SVM method in this case was chosen based on previous research that was widely used for data-based classification.